PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Edward; Jamaludin Khalid (Human Capital Development, 2015)
Purpose- This study was designed to measure the influence of leadership, motivation, and work discipline against work performace Design/methology/approach- The sampling method using Slovin formula to select 50 person of the population. The analysis was done by multiple regression, using SPSS vrsion 20. Findings- Leadership style doesnot influence the work performance of the employee in PT Sinar Jernih Sarana (SJS-Indonesia). The motivation does, but in a weak state, on the other hand, discipline has a main role to influence the performance of the employee. However, when it is done simultaneously, there is a moderate effects on work performance. Research limitations- The strong value of other variables that included in this research is the indicator of the limitation Practical implications- It is strongly suggested to apply the other variables such as compensation, communication, and job satisfaction for the next research. The Originality- The exclusivity research applied in this particular company that discipline is a must.